Rivalry of Issues in the Public Sphere: How are Ecologycal Issues Positioned in the 2019 Political Party campaigns? - Hendy; Yendra Erison; Choirunnisa (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
The aim of this research is to trace environmental issues in the arena of electoral political battles, namely political parties in 2019. The concern so far in electoral political practice, environmental issues in the series of election activities are rarely discussed. As a result, environmental issues are so close to society, as if they have become elite issues as a result of the failure of political parties to bring this issue into the public sphere. The research method in this research is descriptive qualitative with a library research approach. Validation of this research data uses the triangulation method. Researchers collect data through various documents, media or other sources such as books, journals, news, or aggregate data originating from formal institutions such as election bureaucracy institutions and political parties. The research results show that the production of environmental issues presented by political parties in Indonesia is very weak. Environmental issues that should be public issues seem to be private issues. This can be seen in a series of good campaign processes carried out by political parties. Political party campaigns are still minimal and do not even mention environmental issues in their campaigns. Environmental issues, which should be equal to issues of health, education, employment, transportation, politics and security, are being sharply dichotomized in the public sphere. Therefore, the positioning of environmental issues is important for political parties to be involved in public issues that should be so.